Annual health promotion programmes in remote rural Sabah - Naing Oo Tha; San San Win; Than Myint; Ohnmar Thwin; Soong, Hui Fun; D Kamarudin D Mudin (2014)
Health promotion programmes in remote rural areas are conducted annually in Sabah, Malaysia by Faculty of Medicine and Health Science, University Malaysia Sabah. *Objectives* - To understand the concepts and principles of health promotion, to acquire knowledge and skills relevant to the assessment of the community diagnosis by using qualitative and quantitative approaches, to identify the limitation and issues of health promotion and its solution, to formulate the strategic plan and able to conduct the health promotion programme, to empower the rural community to improve rural health through health promotion activities. *Targeted population* is remote rural community. *Stake holders engaged* are UMS, medical and nursing students, local health authorities and rural community. *Methods* - Students were trained by series of lectures for health promotion concepts, approaches and activities and exposed to rural areas in Sabah and conducted practical health promotion programs annually. Students helped empowering the local community to improve their health with multi-approaches Health promotion methods under supervision of a lecturer. Medical and nursing students conducted health promotion programme together in 2 weeks duration . Health and health related problems were identified in selected rural villages .Various types of health promotion activities were conducted in prevention of communicable disease and non-communicable diseases.*Sustainability* - By having sustainable financing , cooperation from stake holders and strong commitment from faculty leadership and team members ,the annual health promotion programmes are conducted effectively in the rural community in Sabah. Although the impact of these health promotion activities cannot be seen in short duration, health issues in the rural community were explained by the students and advise them with causes, risk factors and precautions which would be useful in reducing the occurrence of common health problems in the remote rural areas of Sabah.